Spinal cord injury, Clinical Profile and its Management at Tertiary Care Center in Nepal - Kafle, Prakash; Khanal, Babita; Yadav, Dipak Kumar; Poudel, Deepak; Cherian, Iype (Journal of Nobel Medical College, 2019)
Background: Spinal cord injury causes serious disability among patients. More than 40 million people worldwide suffer from Spinal cord injury every year. Most of them are young men. More than10% of trauma victims sustain spine injury and have higher mortality than other injuries. Materials and Methods: This is a prospective observational hospital based study of traumatic spine injury cases admitted at Nobel Medical College Teaching Hospital, Biratanagr, Nepal from November 2017 to October2018. Results: Total of 352 cases were observed and 36 cases who meet the inclusion criteria for surgical intervention were analyzed. Most common affected age group was between 31-40 years with mean age of 40 years. Out of total cases, 81% were male. Most common cause for spine injury was road traffic accident. Cervical spine was the most common injury (66.7%) and C5- C6subluxation being common radiological diagnosis. ASIA-C neurology status (41.7%) on presentation being most common neurological status. Head injury was the most common associated injury. Anterior cervical discectomy and fusion was the most common surgical procedure performed. Superficial surgical site infections were observed in two cases and hardware failure was seen in one case. Conclusion: The epidemiology of traumatic spine injuries in eastern region of Nepal is similar with other developing countries. In present study, most common cause of spine injury was motor vehicle accidents followed by fall injuries and seen in male. Prevention of road traffic accident might decrease the incidence of spine injury there by reducing the national burden.